Phalaropus fulicarius (Phalaropodidae) - Nahrungserwerb - Rüppell, Georg (IWF (Göttingen), 1968)
Thorshühnchen suchen Nahrung in der planktonreichen Brandungszone vor Spitzbergen. Mit schnellen Pickbewegungen, denen eine orientierende Kopfbewegung vorausgeht, fangen sie Plankton. : The film shows the grey phalarope (Phalaropus fulicarius L.) feeding in the surf area. The bird's abrupt and rapid pecking movements in the plankton-rich sea-water are characteristic.